Policygraphy: Kerangka analisis proses kebijakan dari perspektif non-negara - Sukardi, - (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2002)
What does policy-making look like if we look at it from society, particularly those who are forced to accept whatever the government had decided. This article attempts to over an analytical framework, by taking advantage of etnographic works, the way social capitals being managed and utilized. These attempts are being enhanced through detail process of uncovering the public transcript and the hidden transcript shared and spread out within the community. The working together those processes help to understand how policy process works.